2014
DOI: 10.1371/journal.pone.0101371
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors Have Larger Impact on Endothelial Function in Self-Reported Healthy Women than Men in the HUNT3 Fitness Study

Abstract: BackgroundSeveral studies suggest that cardiovascular risk factors comprising the metabolic syndrome have larger effects on the development of cardiovascular disease in women than in men. A recent study in self-reported healthy subjects demonstrated a marked gender difference in endothelial dysfunction that may be an important precursor of manifest cardiovascular disease. The aim of the present study was to determine whether the association between endothelial function and cardiovascular risk factors is differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 45 publications
1
21
1
Order By: Relevance
“…Their results showed that patients who had mean FMD of 4.4% ± 2.8% developed cardiovascular events like MI, unstable angina, stroke, and death, whereas those without an event had FMD of 7.0% ± 4.9%. Studies by Yu et al, 25 Skaug et al, 26 and Jadhav et al 27 are in agreement with the results of this study. Other studies by Halcox et al 41 and Schächinger et al 42 have also highlighted the significance of endothelial dysfunction in causing predisposition toward acute cardiovascular events like MI by using invasive methods to assess endothelial function.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Their results showed that patients who had mean FMD of 4.4% ± 2.8% developed cardiovascular events like MI, unstable angina, stroke, and death, whereas those without an event had FMD of 7.0% ± 4.9%. Studies by Yu et al, 25 Skaug et al, 26 and Jadhav et al 27 are in agreement with the results of this study. Other studies by Halcox et al 41 and Schächinger et al 42 have also highlighted the significance of endothelial dysfunction in causing predisposition toward acute cardiovascular events like MI by using invasive methods to assess endothelial function.…”
Section: Discussionsupporting
confidence: 93%
“…Based on this concept, FMD can be assessed as an indicator for endothelial dysfunction to gauge the same in the present study. Gokce et al, 24 Yu et al, 25 Skaug et al, 26 and Jadhav et al 27 have observed decreased endothelial function in patients with CVD and in controls. Higashi et al 28 evaluated endothelial function using invasive methods of injecting ACh and nitroglycerin, respectively, to assess vasodilation observed in healthy patients and those with CP and hypertension, whereas endothelial dysfunction was observed in patients with CP and hypertension compared with the control group.…”
mentioning
confidence: 97%
“…10 In vitro and animal studies have shown that inflamma tory cytokines such as TNF are associated with impaired endothelialdependent vasodilatation. 11 Atherosclerotic plaque development On entering the subendothelial layer, LDL undergoes modification in the subendothelial layer, often becom ing oxidized.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…Endothelial function is regulated differently in men and women, with a strong influence of sex hormones. Although women generally have better endothelial function than men, cardiovascular risk factors (blood pressure, poor fitness and metabolic syndrome) are more strongly associated with endothelial function in healthy women without respiratory disease than men . Endothelial function was more strongly associated with High‐Density Lipoprotein (HDL) cholesterol among women in the Framingham Heart study, although it was more strongly correlated with BMI in men .…”
Section: Discussionmentioning
confidence: 99%